2023
DOI: 10.1002/ajcp.12652
|View full text |Cite
|
Sign up to set email alerts
|

Community participation and subjective wellbeing among the immigrant population in Northern Italy: An analysis of mediators

Abstract: Community participation can be a potential strategy to increase the degree of the subjective wellbeing of immigrants within receiving societies. This study aims to analyze the relationship between immigrants' community participation and their subjective wellbeing, testing the two dimensions of sense of mattering (feeling valued and adding value) and psychological sense of community as potential mediators of this relationship. A total of 308 first‐generation immigrants living in Northern Italy filled out a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
1
0
1
Order By: Relevance
“…They can also function as settings where immigrants’ cultural identities are protected and differences are negotiated (Martinez-Damia et al, 2021 ; Marzana et al, 2019 ; Sonn, 2002 ; Taurini et al, 2017 ). In line with this, research found that immigrants who participate within community-based organizations are more integrated and have higher psychological well-being compared with those who do not participate (Martinez-Damia et al, 2023 ; Marzana et al, 2020a , 2020b ). Nevertheless, the liberation of immigrants from oppressive contexts depends on the challenges that MCBOs face when playing their mediating role.…”
Section: Introductionmentioning
confidence: 84%
“…They can also function as settings where immigrants’ cultural identities are protected and differences are negotiated (Martinez-Damia et al, 2021 ; Marzana et al, 2019 ; Sonn, 2002 ; Taurini et al, 2017 ). In line with this, research found that immigrants who participate within community-based organizations are more integrated and have higher psychological well-being compared with those who do not participate (Martinez-Damia et al, 2023 ; Marzana et al, 2020a , 2020b ). Nevertheless, the liberation of immigrants from oppressive contexts depends on the challenges that MCBOs face when playing their mediating role.…”
Section: Introductionmentioning
confidence: 84%
“…El presente trabajo se fundamenta en la información proporcionada por una muestra pequeña de activistas vinculadas a una organización históricamente reciente; sin embargo, contribuye a un campo emergente, interesado en las personas migrantes como agen-tes activos con capacidad para transformar las condiciones opresivas en las sociedades receptoras (Magliano et al, 2016;Martinez-Damia et al, 2023;Marzana et al, 2020;Paloma et al, 2018). De esta manera aporta a la denominada "aproximación de la autonomía de las migraciones" (Mezzadra, 2022), que enfatiza el sentido de agencia y activismo de las personas migrantes como motor de nuevos espacios de ciudadanía que transforman estructuras de dominación en las sociedades receptoras.…”
Section: Introductionunclassified